Pengaruh Kualitas Sustainability Report terhadap Relevansi Nilai Informasi Akuntansi - Nurzi Sebrina; Zulfah Ira Simatupang (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2022)
We examine the effect of the quality of the Sustainability Report on the value relevance of accounting information. The population is all companies listed on the Indonesia Stock Exchange for the 2016-2019 period. Sampling was carried out by purposive sampling which resulted in 60 companies with 4 years of observation (2016-2019). The value relevance of accounting information is carried out by the price model, Ohlson (1995). The quality of the Sustainability Report is measured by a disclosure index based on GRI G4 and GRI Standards. The results show that in 2016-2019 observations, the quality of the Sustainability Report has a negative effect on the value relevance of accounting information. This phenomenon was caused by market anomalies in the value relevance of accounting information in 2019, due to the Covid-19 pandemic, which had an impact on the overall decline in Indonesian stock market prices at the beginning of 2020. In further testing, it was carried out by excluding 2019 observations, and the results were showing an increase in the quality of sustainability reports, increasing the value relevance of accounting information.